Desalination of seawater to provide fresh water - Hawlader, Mohammad Nurul Alam (IIUM Press, 2011)
A comparative study of MSF, MED and RO processes has been made and the relative performance of different methods has been discussed in this study. RO has been showing a great promise, and further developments of new membrane materials and pre-treatment processes are likely to reduce the cost of water production dramatically. MED is making good progress. as shown by reccnt findings, and the production cost of water is less than MSF in certain cases. Cogeneration, water and power, and hybrid system are likely to be the future direction.